Development of a multi‐functional concurrent assay using weak cation‐exchange solid‐phase extraction (WCX‐SPE) and reconstitution with a diluted sample aliquot for anti‐doping analysis. (3rd May 2018) - Kim, Yongseok; Jeon, Mijin; Min, Hophil; Son, Junghyun; Lee, Jaeick; Kwon, Oh‐Seung; Moon, Myeong Hee; Kim, Ki Hun
Abstract : Rationale: In addition to the development of adequate screening methods for multiple compounds, the World Anti‐Doping Agency (WADA) requires anti‐doping laboratories to analyze prohibited substances and their metabolites from various classes. This task presents a difficult challenge for all agencies and interests involved in the field of doping control. Methods: A screening method is reported in which hybrid sample preparation was performed using a combination of weak cation‐exchange solid‐phase extraction (WCX‐SPE) and the 'Dilute and Shoot' strategy in order to take advantage of both the methodologies. Target substances were extracted using a WCX cartridge and reconstituted with a diluted sample aliquot that included 20% of an untreated urine sample. The target substances were further analyzed by high‐performance liquid chromatography/triple quadrupole mass spectrometry (LC/MS). Results: The SPE procedure was optimized using a cartridge‐washing step, elution conditions, and elution volume. The cartridge‐washing step, which was performed using 10% methanol, improved the overall recovery of target substances. Since the recovery was observed to vary according to the pH of the eluting solution, we applied an elution step using both an acid and a basic organic solvent to achieve complementary recovery. Reconstitution of the diluted aliquot sample was performed to recover the polar substances. Conclusions: The method was validated and applied to real samples in accordance with the external quality assessment scheme of WADA and to the previously reported samples that had provided positive test results. This novel method using hybrid sample preparation and LC/MS could be useful to screen multiple classes of the 264 targeted substances in anti‐doping analysis.